Vestibular rehabilitation ameliorates chronic dizziness through the SIRT1 axis - Kao, Chung-Lan; Tsai, Kun-Ling; Cheng, Yuan-Yang; Kuo, Chia-Hua; Lee, Shin-Da; Chan, Rai-Chi (Frontiers in Aging Neuroscience, 2014)
Dizziness is a common clinical symptom frequently referred to general neurologists and practitioners. Exercise intervention, in the form of vestibular rehabilitation, is known as an effective clinical management for dizziness. This intervention is reported to have a functional role in correcting dizziness, improving gaze stability, retraining balance and gait and enhancing physical fitness. Dizziness is known to be highly related to inflammation and oxidative stress. SIRT1 is a major molecule for regulation of inflammation and mitigation of oxidative stress in chronic diseases such as atherosclerosis and chronic obstructive pulmonary disease. However, the bio-molecular roles of SIRT1 involved in the pathogenesis of dizziness are still largely unclear. In this study, a total of 30 subjects were recruited (15 patients with chronic dizziness, and 15 age/gender matched non-dizzy control subjects). The dizzy subjects group received 18 sessions of 30-minutes vestibular training. We found that the mRNA and protein expression levels of SIRT1 in the blood samples of chronic dizzy patients were repressed compared with those of healthy controls. After vestibular training, the dizzy patients had significant symptomatic improvements. The SIRT1 expression and its downstream genes (PPAR-γ and PGC-1α) were upregulated after vestibular exercises in dizzy subjects. Notably, the catalytic activity of SIRT1, NADPH and antioxidant enzyme activities were also activated in dizzy patients after vestibular training. Furthermore, vestibular exercise training reduced oxidative events and p53 expression in patients with dizziness. This study demonstrated that vestibular exercise training improved dizziness symptoms, and mechanisms for alleviation of chronic dizziness may partly involve the activation of the SIRT1 axis and the repression of redox status.